Pre-war life and military career of Douglas Haig - DeGroot, G.J. (University of Edinburgh, 1983)
The existing biographies of Haig pay little attention to his prewar life. This thesis attempts to correct this deficiency. The aim is to offer a complete picture of Haig on the eve of war and to show how his development was shaped by personal, professional and social factors. The thesis has relied mainly on material from the Haig Papers, with additional evidence taken from the manuscripts of Haig's contemporaries. The introduction reviews the existing studies of Haig and discusses the deficiencies of these. The need for a new approach is outlined. Chapter I covers the period from 1861-1879, and deals with Haig's childhood, family background and education, up to and including the period at Clifton. Special emphasis is given to Haig's important relationship with his mother. Chapter II covers the period 1879-1883, when Haig was at Oxford. It analyses the education he received, the life he led and his eventual decision to join the Army. Chapter III deals with the period 1883-1892. It begins with Haig at Sandhurst, and examines the training he received. The remainder of the chapter covers Haig's period as a 7th Hussar, most of which was spent in India. A brief examination of the Victorian Army and in particular the cavalry is included in the chapter. Chapter IV covers the period 1892-1897. Haig left India to compete for the Staff College, but failed the entrance examination. He lobbied to gain entry and was finally admitted in 1896. The chapter analyses the quality and relevance of the training he received during his two years at the College. Chapter V deals with the Sudan Campaign (1897-1898), Haig's first experience of active service. It shows how the experience in the Sudan, though not a positive one for the cavalry, did not alter Haig's faith in the arm. Chapter VI covers the Boer War (1898-1902). This is the most important chapter in the thesis because, as a result of the war, Haig's faith in the cavalry became rigid. The Boer War was the terminus of Haig's development as a soldier; his strategical and tactical beliefs underwent no significant change after 1902. Chapter VII covers 1902-1906, when Haig was Inspector General of Cavalry in India. His development as a soldier now complete, the focus of the thesis is shifted to the consolidation of his position within the Army and to the influential people who aided this consolidation. Chapter VIII deals with 1906-1909, when Haig assisted R. B. Haldane in the program of Army reform. The chapter analyses Haig's contribution to reform. His continued rise, professionally and socially, is charted. Chapter IX covers the period 1909-1914, and focuses on Haig's further rise within the Army. The first two years were spent in India as Chief of Staff, the last two at Aldershot as Ist Corps Commander. Haig's role in the events leading up to the despatch of the B. E. F. for France is studied. The final chapter is an epilogue. A brief summary of the rest of Haig's life is provided. The chapter then shifts to an analysis of the challenges presented by the Great War and examines Haig's ability (based on his pre-war record) to meet them.
The pre-war life and military career of Douglas Haig
Keywords: History